A Novel Technique to Predict Liver Damage After Laparoscopic Gastrectomy From the Stomach Volume Overlapping the Liver by Preoperative Computed Tomography - Kaida, Sachiko; Murakami, Yoko; Ohta, Shinichi; Yamaguchi, Tsuyoshi; Takebayashi, Katsushi; Murata, Satoshi; Nitta, Norihisa; Shimizu, Tomoharu; Tani, Masaji (World journal of surgery, 2020)
Background During laparoscopic gastrectomy (LG), it is necessary to manipulate the lateral segment of the liver to secure the surgical field. Liver retraction during surgery often causes liver dysfunction after LG. However, no previous studies have used preoperative image evaluations to predict postoperative liver damage associated with surgical retraction. We aimed to predict postoperative liver damage after LG. Methods In all, 117 consecutive patients with gastric cancer who underwent LG were included in this study. Using preoperative computed tomography (CT), the volume of the stomach overlapping the liver was integrated and calculated as the liver projecting stomach volume (LPSV). The liver projection ratio (LPR) was calculated by dividing the LPSV by the volume of the whole stomach. The relationships among liver damage, the LPSV and LPR were evaluated. Results A total of 112 patients were divided into two groups as follows: 33 patients in the liver dysfunction group (D group) and 79 patients in the non-dysfunction group (N group). The LPSV was significantly larger in the D group than in the N group (median 77.1 vs 50.1 cm 3 ; p = 0.0061). Similarly, LPR values in the D group were significantly higher than those in the N group (median 33.6 vs 26.2%; p = 0.003). Receiver operating characteristic curve analysis indicated a statistically significant ability of the LPSV and LPR to predict postoperative liver damage (area under the curve; 0.705 and 0.735, respectively). Furthermore, multivariate logistic regression analysis revealed that the increase in the LPR was an independent predictor of postoperative liver damage (odds ratio: 1.042; 95% confidence interval: 1.009–1.078; p = 0.019). Conclusions We have developed a novel technique for predicting postoperative liver damage associated with surgical liver retraction following LG. This method confirms the degree of the LPSV and LPR of the stomach via preoperative CT.